Development and validation of UV-spectrophotometric method for the determination of folic acid in bulk and tablet dosage forms - Takreem A. Elkhazein; Tahani A. Abdeljabar; Amal N. Abdelrahman; Mohamed E. Adam; Shaza W. Shantier (Creative Pharma Assent, 2022)
The purpose of this study was to create and verify a simple and accurate UV-Spectrophotometric technique for determining Folic acid in bulk and tablet dosage form. The approach was based on the measurement of folic acid solution absorbance at 255nm in 0.01M NaOH. In the concentration range of 10-50 g/ml, the constructed calibration curve was found to be linear (R2 = 0.9996). Limits of detection and quantification were 2.73 µg/ml, and 8.27 µg/ml, respectively. The precision of the developed method was confirmed by the obtained low RSD% values. Recoveries percentages were found 98.46%±1.42, 100.0%±0.20, 98.92%±1.12; n=3 for 50%, 100% and 150% levels, respectively indicating the method accuracy and freedom of interference from excipients. Folic acid content percent in the two analyzed brands were found to be equal 96.59%±0.005; n=3, and 97.28%±0.003; n=3 which complies with the official range (90-110%).